The Effect of Stress Management Training with Cognitive Behavioral Style on Stress and Mental Health of Parents of Children with Intellectual Disabilities - Mohammad Nazer; Nasrin Riyahi; Mohammadreza Mokhtaree (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective The birth and presence of a child with mental-retardation in any family causes stress, hopelessness, and disappointment, as well as social, economic, and emotional problems. These problems lead to mental health reduction and using inefficient approaches in family. This research aimed to study the effect of education on mental health and stress rate. Also, it examined the effect of several styles of contrasting stress and stress management program on decreasing stress of parents with mentally-retarded children. Materials & Methods Parents of children with intellectual disabilities in Rafsanjan, Iran (2 health centers) completed Harry stress inventory (HIS) and general health questionnaire (GHQ). A total of 60 couples with high scores in these tests were selected and randomly assigned into 2 groups. Experimental group passed stress management course in 6 sessions for 3 weeks (two sessions per week). The educational contents in 6 sessions were as follows: teaching pathology, semiology, and mental health to parents, then 4 ways of therapeutic approaches of opposition, evasion, continence, and social support, and finally problem solving and practicing those skills. Control group did not receive any treatment. After final session, and then 1 month later, 2 groups completed GHQ and HIS (posttest and follow up). Data were analyzed with repeated measures test. Results Average scores of stress rate in pretest and posttest in the experimental group had a significant difference (P=0.001), but this difference was not significant in follow up test (P=0.659). Average scores of mental health in pretest and posttest of experimental group had significant difference (P=0.001), but this difference was not significant in follow up test (P=0.646). With regard to different aspects of general health, the difference between mean scores of physical signs and depressive signs in pretest and posttest of intervention group was significant (P<0.001). However, the mean scores of anxiety signs and social activity in pretest and posttest was not significant (P=0.13, P=0.07). Conclusion Educating stress management with cognitive–behavioral style could increase the mental health index of parents with mental-retarded children, decrease mothers’ physical and depressive signs, and improve their sleep and social performance. However, in this study, anxiety signs and social activities of parents did not improve. To explain this finding, it can be said that several variables affect the anxiety and social activities of people. And those factors are out of control of this study. These factors are in direct relation with economic situation of people that were not examined in the present research. Also, education stress management with cognitive–behavioral style could reduce perceptive stress of parents. Finally, education causes people, including mothers of mentally-retarded children to know themselves better, recognize their strength and weak points, and reach a level of self-recognition that proceed improving their weak points and promoting their strong points. As a result, parents accept better the reality of their mentally-retarded child and better adapt to this situation. This will in turn reduce the mental stress and increase their health status.